Behind the therapy door: what is "usual care" aphasia therapy in acute stroke management?. Issue 10 (2nd October 2020) - Brogan, Emily; Godecke, Erin; Ciccone, Natalie
ABSTRACT: Background : Usual care is the term used to describe everyday practice in the management of a client within a profession. The knowledge of the tasks used in therapy and key therapeutic processes used within these treatments, provides critical information about if and how the therapy works. The Very Early Rehabilitation in SpEech Randomised Controlled Trial (VERSE RCT) had three arms with therapists within the intensive Usual Care-Plus arm (UC-Plus) providing daily direct aphasia therapy at their discretion for 20 sessions. Aims : To describe usual care aphasia treatment provided in the Usual Care-Plus arm of VERSE RCT. Methods and Procedures : One in four intensive Usual Care-Plus treatment sessions were video-recorded (N = 187) within the main trial. Twenty-five of these (13%) were transcribed, coded, and analysed for therapeutic inputs to describe usual care aphasia therapy using the Template for Intervention Description and Replication (TIDieR) checklist as an overriding framework. Outcomes and Results : Therapy predominantly took place in an inpatient setting (52%) with an average session duration of 51 minutes (SD 7.8). Across the sessions, 96 different tasks were used and 57% of these focused on verbal expression at the single word level. Visual materials were most frequently used compared to the use of technology during sessions. Therapists (n = 16) did the majority of the talking during sessions and most frequently provided models as cues or problem-solving accuracy feedback. Models (55%), sentence completion (51%), and orthographic cues (44%) were the most successful at eliciting the target response. Conclusions : Considerable variability in task selection was seen in the sample which may be a hallmark of usual care. Therapists may have a preference for single word tasks and appear to produce the majority of verbal utterances during sessions, potentially creating an unequal communication environment. This study provided a comprehensive description from the Usual Care-Plus data of the VERSE RCT and may establish a baseline of therapy type for future research.